Metal interactions of α-synuclein probed by NMR amide-proton exchange - Mario Gonzalez-Garcia; Giuliana Fusco; Alfonso De Simone; Alfonso De Simone (Frontiers in Chemistry, 2023)
The aberrant aggregation of α-synuclein (αS), a disordered protein primarily expressed in neuronal cells, is strongly associated with the underlying mechanisms of Parkinson’s disease. It is now established that αS has a weak affinity for metal ions and that these interactions alter its conformational properties by generally promoting self-assembly into amyloids. Here, we characterised the nature of the conformational changes associated with metal binding by αS using nuclear magnetic resonance (NMR) to measure the exchange of the backbone amide protons at a residue specific resolution. We complemented these experiments with 15N relaxation and chemical shift perturbations to obtain a comprehensive map of the interaction between αS and divalent (Ca2+, Cu2+, Mn2+, and Zn2+) and monovalent (Cu+) metal ions. The data identified specific effects that the individual cations exert on the conformational properties of αS. In particular, binding to calcium and zinc generated a reduction of the protection factors in the C-terminal region of the protein, whereas both Cu(II) and Cu(I) did not alter the amide proton exchange along the αS sequence. Changes in the R2/R1 ratios from 15N relaxation experiments were, however, detected as a result of the interaction between αS and Cu+ or Zn2+, indicating that binding to these metals induces conformational perturbations in distinctive regions of the protein. Collectively our data suggest that multiple mechanisms of enhanced αS aggregation are associated with the binding of the analysed metals.